How fashion brands engage on social media: a netnography approach - Loureiro, S. M. C.; Serra, J.; Guerreiro, J. (Journal of Promotion Management, 2019)
This study compares how fashion brands communicate on social media. A netnography study analyzed six global brands during a 6-month period. Results show that fast-fashion brands emerge as the most effective in online communication. Haute-couture brands are very similar in the way they communicate and show a good level of interactivity with their consumers. However, sports brands have a low level of communication overall and show a low number of photos and videos. The most successful fashion brands continually update photos and videos, interact with consumers, and make them feel a part of the brand by using celebrities.